Comparison of the Effectiveness of Acceptance and Commitment Therapy and Solution-Focused Therapy on Marital Quality of Life and Sexual Communication Intelligence in Couples with Marital Conflicts - Amiri, Zohreh; Norouzi, Asghar; Abolghasemi, Shahnam (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Solution-Focused Therapy (SFT) on marital quality of life and sexual communication intelligence in couples experiencing marital conflicts. Methods: This study was applied in terms of its objective and employed a quasi-experimental design with a pretest-posttest structure, a two-month follow-up, and a control group for data collection. The statistical population consisted of all couples aged 25 to 40 who had marital conflicts and visited counseling and psychology clinics in District 13 of Tehran in 2023. From this population, 45 couples were selected using purposive sampling. The research instruments included the Sexual Communication Intelligence Questionnaire (Dehkordi et al., 2021) and the Marital Quality of Life Questionnaire (Babci et al., 1995), which were completed by the couples. One group underwent Solution-Focused Therapy in eight 90-minute sessions, while the other group received Acceptance and Commitment Therapy in ten 90-minute sessions. Data analysis was conducted using repeated measures ANOVA in SPSS software. Findings: The results indicated that Acceptance and Commitment Therapy had a positive effect on marital quality of life and sexual communication intelligence. Additionally, Solution-Focused Therapy was also effective in improving these two components (p < .05). Conclusion: The findings of this study demonstrate the effectiveness of both therapeutic approaches—Solution-Focused Therapy and Acceptance and Commitment Therapy—on marital quality of life and sexual communication intelligence. A comparison of the two methods revealed that Acceptance and Commitment Therapy was more effective than Solution-Focused Therapy.